BIOCONVERSION PROPERTY OF TEA LEAVES WASTE BY Aspergillus niger AS FUNCTIONAL FIBER TO DECREASE BLOOD LIPID - Hernaman, I.; Kamil, K.A.; Tanuwiria, U.H.; Lestari, E.S.; Toharmat, T. (Journal of the Indonesian Tropical Animal Agriculture, 2010)
This research was aimed to find out the change of tea leaves waste fiber on lipid absorption afterbeing fermented by Aspergillus niger and also to be expected as a model to gain healthy livestockproduct. Tea leaves waste was fermented by Aspergillus niger during 6 day. Fifteen of rats with initialweight of 41.17±4.05 g were fed ad libitum by diets containing different levels of unfermented andfermented tea leaves waste as follows: basal diet (R1), unfermented tea leaves waste 5% (R2),unfermented tea leaves waste 10% (R3), fermented tea leaves waste 5% (R4), fermented tea leaveswaste 10% (R5). The results indicated that bioconversion of tea leaves waste in diet (R4 and R5)decreased almost all of fiber fractions (NDF 75.55%; ADF 57.17%; celluloses 26.74%; lignine 31.19%),except hemicelluloses 18.38%, while the treatment did not change the lipid binding rate (2.07 vs 1.98).Also, the result showed that rats fed with diets containing fermented tea leaves waste (R4 and R5) hadreduced cholesterol (86.25;87.4 mg/dl) and triglyceride (47.06; 46.03 mg/dl), but not on HDLcholesterol(29.28; 26.51 mg/dl). It was concluded that bioconversion property of tea leaves waste byAspergillus niger changed fiber fraction and decreased blood lipid.